2021
DOI: 10.3389/fimmu.2021.781718
|View full text |Cite
|
Sign up to set email alerts
|

GII.P16-GII.2 Recombinant Norovirus VLPs Polarize Macrophages Into the M1 Phenotype for Th1 Immune Responses

Abstract: Norovirus (NoV) is a zoonotic virus that causes diarrhea in humans and animals. Outbreaks in nosocomial settings occur annually worldwide, endangering public health and causing serious social and economic burdens. The latter quarter of 2016 witnessed the emergence of the GII.P16-GII.2 recombinant norovirus throughout Asia. This genotype exhibits strong infectivity and replication characteristics, proposing its potential to initiate a pandemic. There is no vaccine against GII.P16-GII.2 recombinant norovirus, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have demonstrated that VLPs effectively promoted the phenotypic maturation of macrophages, which present VLP antigens to naïve CD4 + T cells and induce the differentiation of Th0 cells toward Th1 and Th2 phenotypes ( 52 ). Accordingly, Hexa-VLPs elicited mixed Th1/Th2 responses signified by high-level IFN-γ, TNF-α, IL-2 and IL-4 positive T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that VLPs effectively promoted the phenotypic maturation of macrophages, which present VLP antigens to naïve CD4 + T cells and induce the differentiation of Th0 cells toward Th1 and Th2 phenotypes ( 52 ). Accordingly, Hexa-VLPs elicited mixed Th1/Th2 responses signified by high-level IFN-γ, TNF-α, IL-2 and IL-4 positive T-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…The GSEA enrichment analysis showed that gene sets grouped according to IGSF6 expression were mainly enriched in cytokine-receptor interaction and intercellular interaction. It has been well established that antigen peptide-MHCII complex presented by macrophages and DCs is essential for the activation of Th1 cells [28][29][30][31]. Previous studies have also proposed that IGSF6 may be closely related to antigen uptake, or the recirculation of DCs [13].…”
Section: Discussionmentioning
confidence: 99%
“…The GSEA enrichment analysis showed that gene sets grouped according to IGSF6 expression were mainly enriched in cytokine-receptor interaction and intercellular interaction. It has been well established that antigen peptide-MHCII complex presented by macrophages and DCs is essential for the activation of Th1 cells [27][28][29][30]. Previous studies have also proposed that IGSF6 may be closely related to antigen uptake, or the recirculation of DCs [13].…”
Section: Discussionmentioning
confidence: 99%